2022
DOI: 10.1002/cjoc.202200220
|View full text |Cite
|
Sign up to set email alerts
|

Isosteroidal Alkaloids from Fritillaria verticillata Willd. and Their NMR Spectroscopic Characteristics

Abstract: Chemical investigation of Fritillaria verticillata Willd. led to the isolation of eight novel isosteroidal alkaloids (1-4, 6, 9-11) and four known alkaloids (5, 7-8, 12), including three unprecedented cis-fused D/E (13α, 17α) cevanine alkaloids (1-3), one rarely cis-fused E/F (22α) cevanine alkaloid (6), and one uncommon 5β-jervine-type isosteroidal alkaloid featuring a cis-fused A/B ring moiety (11). In order to establish the structures of 1, the calculated NMR with DP4+ evaluation was applied from the plausi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…When the lone-pair electrons on the nitrogen atom is in α- orientation and H-22 is in β-orientation (Figure S142, structure C/D ), and when the 21-Me is on the same side (α-orientation) with lone-pair electrons, the carbon signals around the nitrogen atom would show the same abnormal shapes as for structure A (Figure S142), in CD 3 OD, such as for compounds 5 and 9 . Previously, Ma has summarized some NMR characteristics of cevanine-type alkaloids without OH at C-20 and concluded that regardless of whether the lone-pair electrons on the nitrogen atom were β-oriented or α-oriented, all the α-C and α-H signals around the nitrogen atom were unobserved in CD 3 OD, even those correlations in HSQC, HMBC, and NOESY. By analysis of the NMR data and the structures of compounds 1 – 6 and 9 – 12 (Figure S145), we have further expanded these analyses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the lone-pair electrons on the nitrogen atom is in α- orientation and H-22 is in β-orientation (Figure S142, structure C/D ), and when the 21-Me is on the same side (α-orientation) with lone-pair electrons, the carbon signals around the nitrogen atom would show the same abnormal shapes as for structure A (Figure S142), in CD 3 OD, such as for compounds 5 and 9 . Previously, Ma has summarized some NMR characteristics of cevanine-type alkaloids without OH at C-20 and concluded that regardless of whether the lone-pair electrons on the nitrogen atom were β-oriented or α-oriented, all the α-C and α-H signals around the nitrogen atom were unobserved in CD 3 OD, even those correlations in HSQC, HMBC, and NOESY. By analysis of the NMR data and the structures of compounds 1 – 6 and 9 – 12 (Figure S145), we have further expanded these analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, l -cysteine methyl ester (2.5 mg) was added to the aqueous layer of compound 7 in anhydrous pyridine (1 mL). And the mixture was kept at 60 °C for 1 h. Next, arylisothiocyanate (200 μL) was added to the reaction mixture and reacted at 60 °C for 1 h . After completion of the reaction, the products were analyzed by HPLC chromatography.…”
Section: Methodsmentioning
confidence: 99%
“…The unique aromatic ring structure of sipeimine gives the bulb its medicinal value and helps it exert curative effects in lung moisturizing, cough relief and phlegm elimination. 8 F. taipaiensis is found in alpine grasslands, meadows and scrub meadow areas at altitudes ranging from 2000 to 3000 m. As a valuable traditional Chinese medicine, the wild variety F. taipaiensis E.B (EB) faces restricted production and limited availability 9 due to environmental influences. Consequently, EB is scarce in the market.…”
Section: Introductionmentioning
confidence: 99%
“…The main active ingredient in the bulb is sipeimine, which belongs to the group of isosteroidal alkaloids. The unique aromatic ring structure of sipeimine gives the bulb its medicinal value and helps it exert curative effects in lung moisturizing, cough relief and phlegm elimination 8 …”
Section: Introductionmentioning
confidence: 99%